RELEVANSI BUDAYA ORGANISASI DAN EFEKTIVITAS SEBUAH PERUSAHAAN: STUDI PADA RESHARE RABBANI CABANG MALANG RAYA - ROULITA FIRDA AZMI; RAHMAD HAKIM; NURUL ASFIAH (Maqdis: Jurnal Kajian Ekonomi Islam, 2019)
This research aims to describe the relevance of organizational culture in creating corporate effectiveness at Reshare Rabbani Malang Branch. Reshare Rabbani has an unique strategies that different from other companies. By using qualitative research, through in-depth interview, documentation and observation, data were analyzed descriptively with a case study approach. The results of this study indicate that the culture adopted by Reshare Rabbani is a strong culture, depicted by the values that are deeply embedded in the members of the organization, based on the value of Tawheed, grateful, never giving up, continuous improvement, caring in every circumstance and high responsibility. Organizational culture at Reshare Rabbani is relevant to the creation of company effectiveness’ indicators; a production system that focuses on quality, created satisfaction, intertwining harmony between employees, adaptation, growth and fulfillment level of efficiency.